Réponses

2014-05-06T19:46:15+02:00
Bonjour
f est une fonction affine 
f(x) = ax+b
on connait 
f(2) = 11                               et               f(-3) = -26.5             soit
2a+b = 11                            et                -3a + b = -26.5
b = 11 - 2a     on remplace                      -3a + (11 - 2a) = -26.5 
                                                             -5a = -26.5 - 11 
                                                             -5a = -37.5 
                                                              a = -37.5 / -5 = 7.5 
b = 11 - 2(7.5) 
b = - 4
la fonction sera f(x) = 7.5x - 4 
  • Utilisateur Brainly
2014-05-06T19:51:40+02:00
Fonction affine =ax+b

f4(2) = 11 s'ecrit  2a+b = 11
f4(-3) = -26,5 ... -3a+b = -26,5

systeme à résoudre

2a+b = 11
-3a+b = -26,5

-1(2a+b) = 11
-3a+b = -26,5
15/2
-2a-b = -11
-3a+b = -26,5
-5a = - 37,5
a = 15/2

2a+b = 11
30/2+b = 11
b = -15+11
b = -4

f4 = 15x/2-4